A risk-based soft sensor for failure rate monitoring in water distribution network via adaptive neuro-fuzzy interference systems - Gheibi, Mohammad; Moezzi, Reza; Taghavian, Hadi; Wacławek, Stanisław; Emrani, Nima; Mohtasham, Mohsen; Khaleghiabbasabadi, Masoud; Koci, Jan; Yeap, Cheryl S Y; Cyrus, Jindrich (Scientific reports, 2023)
Water Distribution Networks (WDNs) are considered one of the most important water infrastructures, and their study is of great importance. In the meantime, it seems necessary to investigate the factors involved in the failure of the urban water distribution network to optimally manage water resources and the environment. This study investigated the impact of influential factors on the failure rate of the water distribution network in Birjand, Iran. The outcomes can be considered a case study, with the possibility of extending to any similar city worldwide. The soft sensor based on the Adaptive Neuro-Fuzzy Inference System (ANFIS) was implemented to predict the failure rate based on effective features. Finally, the WDN was assessed using the Failure Modes and Effects Analysis (FMEA) technique. The results showed that pipe diameter, pipe material, and water pressure are the most influential factors. Besides, polyethylene pipes have failure rates four times higher than asbestos-cement pipes. Moreover, the failure rate is directly proportional to water pressure but inversely related to the pipe diameter. Finally, the FMEA analysis based on the knowledge management technique demonstrated that pressure management in WDNs is the main policy for risk reduction of leakage and failure.